Thermostimulated luminescence of SrB₄O₇:Eu²⁺ single crystals - Yavetskiy, R.P.; Dolzhenkova, E.F.; Tolmachev, A.V.; Parkhomenko, S.V.; Baumer, V.N. (Functional Materials, 2006)
Thermallystimulated luminescence (TSL) of SrB₄О₇:Eu²⁺ single crystals irradiated with у and X-ray quanta has been studied for the first time and compared with that of SrB₄О₇ crystals. The induced optical absorption in the 400 to 700 nm region has been ascribed to 1s → 2р transitions of F⁺ centers. The Eu²⁺ ions have been shown to act simultaneously as traps and as radiative recombination of charge carriers. Basing on the TSL, optical absorption, and photoluminescence studies of SrB₄О₇:Eu²⁺ single crystals, a TSL mechanism has been proposed associated with the decay of F⁺ centers being in non-equivalent crystallographic positions followed by radiative recombination of charge carriers on europium ions. Possible positions of the localization of radiation-induced defects in the SrB₄О₇ crystal structure has been discussed.